HUBUNGAN KELINCAHAN, KELENTUKAN, KECEPATAN DAN KOORDINASI DENGAN KETERAMPILAN MENGGIRING BOLA DALAM PERMAINAN SEPAKBOLA - Bismar, Ahmad Rum; Fadillah, Arman (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This study aims to determine the relationship of the relationship between agility, flexibility, speed and coordination with dribbling skills in football games. This research is a descriptive correlational type of research. The study population was all male students of class XI of SMA Negeri 2 Makassar with a total sample of 150 male students who were selected by random sampling. The data analysis technique used is a single correlation analysis technique and the correlation of four predators. Based on the results of data analysis, this study concluded that: There was a significant relationship between agility and dribbling skills in football, (ro = 0.508> rt = 0.220); There is a significant relationship between flexibility and dribbling skills in football, (ro = 0.693> rt = 0.195); There is a significant relationship between speed and dribbling skills in football (ro = 0.693> rt = 0.195); There is a significant relationship between coordination with dribbling skills in the game of football (ro = 0.693> rt = 0.195); There is a significant relationship between agility, flexibility, speed and coordination with dribbling skills in football (ro = 0.693> rt = 0.195).